The Effect of the Learning Model "Problem Based Learning" on Interpersonal Intelligence and Student Pancasila and Civic Subject Learning Outcomes - Ramadhani Lastari; Daulat Saragi; Abdul Murad (Randwick International of Education and Linguistics Science Journal, 2023)
To find out the factors that can determine student learning outcomes and measure students' interpersonal intelligence in PANCASILA AND CIVIC EDUCATION subjects in class IV 8 Langkat students with the theme 1 Beautiful togetherness and sub -theme 1 Diversity of my nation's culture in the PBL learning model. . Researchers use quasi experimental design because in this study there are variables from outside that cannot be controlled by researchers. The design used in this study is the two group pretest-post-test design. The researcher conducted a normality and homogeneity test assisted using SPSS 26.0. Data Pretest and Posttest Learning Outcomes Based on the Normality Test. The results show that the experimental and control classes have a significance value of greater than 0, 05. Data Pretest and Learning Outcomes Based on the homogeneity test in Table 4 obtained a significance value greater than 0.05 (0, 47> 0.05). Interpersonal intelligence and learning outcomes of students who are taught with the problem based learning model are better than students who are taught with direct learning models (direct instruction). There is a positive relationship between interpersonal intelligence and student learning outcomes taught with a problem based learning model. The increase in learning outcomes was 0.41 (medium) and an increase in the interpersonal intelligence of students was 0.55 (medium).